Aesthetic surprises and considerations when researching marine science education with art - Hannigan, Shelley M.; Freitas, Cátia; Francis, Prue (Frontiers in Education, 2023)
Introduction Why was the study undertaken? What was the research question, the tested hypothesis or the purpose of the research? The research question is: What are the implications of disciplinary aesthetics when marine science meets art in educational research? Children in schools from Victoria, Australia were engaged in a series of marine science fieldtrips, workshops and lessons based on the Great Southern Reef, a temperate marine environment of Australia. They created drawings based on provocations, to depict their knowledge of marine species, before and after these education experiences. Methods When, where, and how was the study done? What materials were used or who was included in the study groups (patients, etc.)? This paper shares the mixed methodology used by focusing on the qualitative methods used, that arose out of a need to understand the role of aesthetics in this research project. This paper documents the analysis of data that included children’s drawings and dialogue between researchers and children from interviews. We discuss insights into the role of aesthetics that were revealed in the visual and narrative data from perspectives of children’s learning and how the researchers were able to understand this. These findings are discussed considering the teaching intentions and procedures used, the importance of this multimodal approach to research that revealed aesthetics of science, visual art and language in education. Results What answer was found to the research question; what did the study find? Was the tested hypothesis true? The research reveals the important role drawing has when trying to understand the students’ varying degrees of understanding marine science education. Variables include: their prior experience with marine environments, students’ drawing abilities, stylistic elements (that can render an image ‘confident’ or ‘sketchy’), compositional devices and use of perspective that their drawings depict (looking at a pier from underwater or through snorkel goggles). It also includes interpretations and explanations of their drawings and other uses of language such as the use of written labels to reinforce or clarify parts of their drawings. Discussion What might the answer imply and why does it matter? How does it fit in with what other researchers have found? What are the perspectives for future research? This research reveals the important role of multi-modal approaches in science learning and the significant and dependent role of visual art and words, for students to communicate their learnt content knowledge. It highlights the aesthetic experiences that must be taken into consideration when teaching, learning and when understanding what has been learnt.